Some Afforestation Problems in the Punjab Plains - Hamilton, A. P. F. (Indian Forester, 1946)
Although the localities dealt with lie in the "under 10 inches" rain belt, they differ from the greater part of the desert fringe tract, for which a series of afforestation experiments are being undertaken by the Punjab forest department under the direction of the Central Silvicuiturist, in that the water table is high and rivers flow at no great distance. Nevertheless there are certain soil types of a highly refractory nature which present real problems.